2021
DOI: 10.1128/spectrum.00087-21
|View full text |Cite
|
Sign up to set email alerts
|

Mild SARS-CoV-2 Illness Is Not Associated with Reinfections and Provides Persistent Spike, Nucleocapsid, and Virus-Neutralizing Antibodies

Abstract: This article demonstrates that people who have mild COVID-19 illnesses and produce antibodies are protected from reinfection for up to 6 months afterward. The antibodies that people produce in this situation are stable for up to 6 months as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…Comparing studies that used sampling methods that detected people with no or mild symptoms ( 27 , 31 , 35–37 ) with those that recruited only symptomatic people ( 25 , 26 , 28 , 33 ) did not show a clear relationship between recruitment method and protection against reinfection. A recently published cohort study found that mild COVID-19 was associated with protection against reinfection and generally supports our conclusions, although no reinfections were observed and the sample was relatively small ( 23 ).…”
Section: Resultssupporting
confidence: 90%
“…Comparing studies that used sampling methods that detected people with no or mild symptoms ( 27 , 31 , 35–37 ) with those that recruited only symptomatic people ( 25 , 26 , 28 , 33 ) did not show a clear relationship between recruitment method and protection against reinfection. A recently published cohort study found that mild COVID-19 was associated with protection against reinfection and generally supports our conclusions, although no reinfections were observed and the sample was relatively small ( 23 ).…”
Section: Resultssupporting
confidence: 90%
“… ELISA; Anti-RBD IgG tested by an uncommercially kit following the Krammer laboratory protocol Unadjusted RR b 8 (HQ) 16 Sebastian Havervall et al, 2021 [ 56 ] 300 HCWs in Stockholm, Sweden Median (IQR) 46 (35-54) 2020.04.09-2021.02.26 10.6 A positive PCR result detected more than 7 months after a baseline seropositive result. Luminex; Anti-S IgG tested by a bead-based high-throughput multiplex assay based on the FlexMap3D (Luminex Corp.) platform Unadjusted RR b 5 (MQ) 17 Charles F Schuler 4 th et al, 2021 [ 57 ] 653 subjects were either HCWs or patients with a high risk of exposure to COVID-19 in Michigan, USA Median (IQR) 41 (31-51) 2020.05-2021.02 9.0 A positive PCR result detected after a baseline seropositive result. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, differentiation between persistent COVID-19 and reinfection is challenging, in particular in older persons ( Ringlander et al, 2021 ). It is also not entirely clear whether disease severity of the initial SARS-CoV-2 infection significantly modifies the risk of reinfections, but it should be noted that even asymptomatic SARS-CoV-2 infections elicit a strong immunological response ( Boyton and Altmann, 2021 ; Garrido et al, 2021 ; Murillo-Zamora et al, 2021a ; Schuler et al, 2021 ; Spicer et al, 2021 ).…”
Section: Efficacy and Duration Of Natural Immunity Against Reinfectionsmentioning
confidence: 99%